Kontakty polsko-islandzkie po 1945 r. - Romański, Mirosław (Przegląd Nauk Historycznych, 2012)
The text entitled Polish-Icelandic contacts after 1945 presents previously unknown closer relations between the two countries, ie Poland and Iceland after the World War II. In this paper the author tried to present a general relationship between the two countries, focusing on all major fields of cooperation, namely on diplomatic, political, economical and cultural relations. Turning points of the text are justified, because renewal of these contacts occurred after 1945, and the cooperation between mentioned countries exists virtually to the present day. Of course, they looked different then, and on other planes Poland cooperates with Iceland today. Although there were a few texts concerning the studied subject, but they focus more on cultural contacts and Icelandic government’s politics on the employment of Poles in this country. For example, the matter of political cooperation and the attitude of the Polish People’s Republic towards the Icelandic policy have not been widely discussed. The source collections concerning discussed subject acquired Archives of New Records in Warsaw, where we could find the Polish and English documents on Polish cooperation with Iceland in the period. On this basis the author was able to reproduce the conditions and character of these relations. Preliminary archival research was enriched with press sources, but despite their impressive numbers, the information contained in them are often duplicated by different authors. Undoubtedly topics discussed in this article can be a contribution to do more research in this area, to which the author warmly encourages everyone interested in the subject.